Biological agents for synthesis of nanoparticles and their applications against plant pathogens - Pandit, Chetan; Roy, Arpita; Ghotekar, Suresh; Khusro, Ameer; Islam, Mohammad Nazmul; Emran, Talha Bin; Lam, Siok Ee *; Khandaker, Mayeen Uddin *; Bradley, D.A. * (Elsevier, 2024)
In terms of cost-efficiency, biocompatibility, environmental friendliness, and scalability, green nanoparticle (NP) synthesis is a novel field of nanotechnology that outperforms both physical and chemical approaches. Plants, bacteria, fungi, and algae have lately been used to produce metals and metal oxide nanoparticles as an alternate method. The development of alternative strategies to restrict the growth of hazardous bacteria, as well as the building of resistance by germs to various antibiotics, led to the introduction of nanoparticles as novel antimicrobial agents. Metal oxides have been found to form oxide monolayer structures for drug delivery when they react with a transporter's surface. Metal oxide nanoparticles have emerged as biomedical materials in recent years, with applications in immunotherapy, tissue treatment, diagnostics, regenerative medicine, wound healing, dentistry, and biosensing platforms. Biotoxicology and its antimicrobial, antifungal, and antiviral characteristics were hotly contested. Metal oxide nanoparticles have tremendous applicability and commercial value, as evidenced by important discoveries in the realm of nanobiomedicine in terms of locations and amounts. This paper describes the production of nanometal oxides from various green materials, as well as their applications.